The asymmetry of pectoralis muscles is greater in male prepubertal than in professional tennis players. Issue 7 (2nd October 2016) - Sanchis-Moysi, Joaquin; Dorado, Cecilia; Idoate, Fernando; González-Henríquez, Juan J.; Serrano-Sanchez, Jose A.; Calbet, Jose A. L.
Abstract: It is generally accepted that preadolescents have a limited capacity to develop muscle hypertrophy in response to exercise compared with older populations; however, studies are scarce and conflicting. The main aim of the present study was to assess if playing tennis is associated with the hypertrophy of dominant pectoralis muscles (PM) in professional (PRO) and in prepubescent tennis players (PRE). A secondary aim was to assess if the degree of asymmetry of PM is greater in PRO than PRE. The volume of PM of both sides was determined using magnetic resonance imaging in 8 male PRO (21.9 years), 6 male PRE (11 years, Tanner 1–2) and 12 male non-active controls (6 adults: 23.5 years; and 6 prepubescents: 10.7 years, Tanner 1–2). PRO and PRE had 15 and 30% greater volume, respectively, in the dominant than in the contralateral PM ( P < .01). No significant side-to-side differences in PM volume were observed in the non-active controls (3%, P = .34 in adults and 5%, P = .17 in children). The degree of side-to-side asymmetry in PM volume was greater in PRE than in PRO ( P < .05). In conclusion, tennis practice is associated with marked hypertrophy of dominant PM in tennis players, even at prepubertal age, whilst non-active age-matched control subjects display similar volumes in both sides. The larger asymmetry observed in PRE than in PRO may indicate a greater relative loading in the children or increased contralateral hypertrophy in the professionals. This study demonstrates that prepubertal children respond with marked hypertrophy to loading by tennis.